Audit Committee, Auditor Tenure and Company Size: Implications for The Integrity of Financial Reports - Pitria, Indah; Miftah, Desrir (Basecamp Economics PubMed, 2024)
The discovery of company dishonesty in disclosing financial reports can have a negative impact on interested parties because it can be misleading in decision making due to inaccurate information presented. This research aims to determine the influence of the Audit Committee, Audit Tenure, and Company Size on the Integrity of Financial Reports in Insurance Sub-sector Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research uses quantitative methods. The sample in this study was selected using a purposive sampling technique and obtained 68 analysis units from 17 companies. Data analysis in this research uses panel data analysis. The results of this research indicate that the Audit Committee and Audit Tenure have a negative effect on the integrity of financial reports, while company size has no effect on the integrity of financial reports.